Effects of probiotics on body weight, body mass index, fat mass and fat percentage in subjects with overweight or obesity: a systematic review and meta‐analysis of randomized controlled trials - Borgeraas, H.; Johnson, L. K.; Skattebu, J.; Hertel, J. K.; Hjelmesæth, J. (Obesity reviews, 2018)
Summary A systematic review and meta‐analysis of randomized controlled trials was conducted to examine the effects of probiotic supplementation on body weight, body mass index (BMI), fat mass and fat percentage in subjects with overweight (BMI 25–29.9 kg m−2) or obesity (BMI ≥30 kg m−2). MEDLINE, EMBASE and the Cochrane Central Register of Controlled Trials were searched for studies published between 1946 and September 2016. A meta‐analysis, using a random effects model, was performed to calculate the weighted mean difference between the intervention and control groups. Of 800 studies identified through the literature search, 15 were finally included. The studies comprised a total of 957 subjects (63% women), with the mean BMI being 27.6 kg m−2 and the duration of the interventions ranging from 3 to 12 weeks. Administration of probiotics resulted in a significantly larger reduction in body weight (weighted mean difference [95% confidence interval]; −0.60 [−1.19, −0.01] kg, I2 = 49%), BMI (−0.27 [−0.45, −0.08] kg m−2, I2 = 57%) and fat percentage (−0.60 [−1.20, −0.01] %, I2 = 19%), compared with placebo; however, the effect sizes were small. The effect of probiotics on fat mass was non‐significant (−0.42 [−1.08, 0.23] kg, I2 = 84%).